Investigating magnetically targeted microbubbles for ultrasound-enhanced thrombolysis - de Saint Victor, M (2016)
Despite therapeutic advances, ischaemic stroke remains one of the leading causes of mortality and disability worldwide. Microbubble-enhanced sonothrombolysis is an advantageous method to accelerate the reopening of occluded arteries, but further improvements in safety and efficacy are required to attain widespread clinical implementation. This thesis investigates the potential of magnetically targeted microbubbles to enhance sonothrombolysis. First, a computational and experimental model of a thrombosed vascular network was developed. It showed that magnetic targeting considerably increases the number of microbubbles delivered to the thrombus, a key element for effective sonothrombolysis. The effect of these magnetically targeted microbubbles on rates of thrombus breakdown was then investigated in vitro, first with ultrasound and microbubbles alone (mechanical sonothrombolysis), then with the addition of fibrinolytic drugs (enzymatic sonothrombolysis). Magnetic targeting was not found to affect mechanical treatment, and mechanical lysis rates were highly variable. On the other hand, magnetic targeting significantly accelerated enzymatic treatment, even with low concentrations of fibrinolytic drugs. The mechanisms underlying both treatments were discussed. In addition, treatment safety was examined. Specifically, the risk of secondary embolism and the feasibility of real-time treatment monitoring were assessed. Neither treatment increased the risk of downstream vascular embolism with large clot fragments. Acoustic monitoring of enzymatic sonothrombolysis was feasible, as a strong correlation was found between lysis rates and the energy of acoustic emissions near the clot surface. There was no strong correlation in mechanical sonothrombolysis. Magnetic targeting may therefore be regarded as a promising adjuvant to enzymatic sonothrombolysis, improving microbubble delivery to the clot, accelerating its breakdown, and reducing injected drug doses. It is hoped that targeted treatment and real-time monitoring will enhance safety and efficacy in the management of acute and chronic thrombosis, and ultimately improve patient outcomes.